GENDER ATTITUDES OF PERCEPTION AND BUILDING A MARKETING STRATEGY - YEVCHENKO, Veronika; KUZEMKO, Andriy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article substantiates the need for a gender approach to the analysis and regulation of consumer behavior. In particular, the article discusses gender peculiarities of consumer behavior, including gender roles and gender stereotypes. The peculiarity of consumer behavior is that the regularities of the human psyche are often not realized. While survey results can mostly be analyzed and controlled, psychophysiological reactions are almost impossible to control.We are constantly in the information space. Given the rapidly changing environment and the emergence of modern technologies, we receive and process a huge amount of information around us (advertising, signs, communication with friends and family, news, etc.). The entire flow of information is perceived by a person according to simplified schemes. Sometimes we simply make decisions based on invisible algorithms or habits without even analyzing the source data, relying on ready-made behavioral patterns. And this makes us very predictable and easy to manage, provided that we have the right algorithms for action. First of all, we are talking about the stereotypes of society (some are clear and proven in the historical sense, others are just being formed, and still others are subject to change). Gender perceptions are among those that can be attributed to stereotypes that have the ability to influence the consumer, the manufacturer and shape the marketing strategy. Differences between "male" and "female" products are expressed through gendered visual codes and communication based on gender stereotypes.For many years, companies have been using marketing to convince both children and adults that there are products for their own gender and for the opposite gender, and our society tends to hold on to the stereotypes it is used to. Perhaps if we focus on the interests of a person and the important qualities of the product rather than their gender when choosing a purchase, we can, first, spend less money, and second, see that there are not as many real differences between the sexes as we used to think.
Keywords: gender marketing; product promotion; consumer behavior; marketing strategy; stereotypes